Degradation of organic dyes in water by electrical discharges - Magureanu, Monica; Mandache, Nicolae Bogdan; Parvulescu, Vasile I. (Plasma chemistry and plasma processing, 2007)
The degradation of several organic compounds in aqueous solution: methyl yellow (C14H15N3), methyl red (C15H15N3O2), methyl orange (C14H14N3NaO3S), phenol red (C19H14O5S) and methylene blue (C16H18ClN3S), was investigated in a pulsed corona discharge. High voltage pulses of 17 kV amplitude, 24 ns rise time and approximately 200 ns duration (full width at half maximum-FWHM) were applied to an array of six hollow needles. When oxygen was bubbled into the solution through the needle, current pulses of 90 A amplitude were obtained and the average power dissipated in the discharge was 19 W at 100 Hz pulse repetition rate. UV-visible spectra of the aqueous solutions show a significant reduction of the absorbance in the visible range, up to 90%, after plasma treatment, suggesting fragmentation of the compounds. Several aliphatic compounds were identified as oxidation products of methyl yellow, methyl red and methyl orange. For methylene blue and phenol red aromatic reaction products were detected as well.